THE CALM BEFORE THE STORM AND THE STORM BEFORE THE CALM: A CASE OF RETRACTABLE THYROID STORM - A, Mohd Hazriq; M, Aimi Fadilah; EW, Nur Aini; Z, Aisyah; MS, Fatimah Zaherah; AG, Rohana (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Thyroid storm is a severe complication of hyperthyroidism with a high mortality rate. Multimodal pharmacotherapy is the cornerstone of treatment. In severe cases, plasmapheresis may also be done. However, this practice is not widespread with a lack of clear guidelines. CASE We describe a 37-year-old female with severe thyroid storm and multiple organ failure. She initially presented with a three-week history of worsening jaundice, dyspnea and pedal edema. At presentation, she was neurologically intact but had prominent jaundice, congestive heart failure, atrial fibrillation, goiter and mild thyroid ophthalmopathy. Tests revealed elevated FT4 >90 pmol/L, TSH <0.01 mIU/L, bilirubin 267 µmol/L and coagulopathy. With a BurchWatforsky Point Scale of 65, full pharmacotherapy for thyroid storm was promptly instituted. Due to lack of clinical improvement and rising bilirubin, we resorted to plasmapheresis after seven days with a view for early thyroidectomy. Plasmapheresis was administered over three sessions and resulted in normalization of FT4 (14.32 pmol/L), resolution of heart failure, and improvement of bilirubin and other blood parameters. Three days later, sensorium quickly deteriorated to coma requiring intubation. EEG showed nonconvulsive seizure; other neurologic investigations were non-contributory. Her condition was further complicated with retractable arrythmia, worsening coagulopathy with lower gastrointestinal bleed, and rising FT4 level and liver function tests. Four further courses of plasmapheresis were administered to control FT4, with improvement in other biochemical markers, subsequent resolution of seizure and recovery of consciousness. This allowed a safe window for urgent thyroidectomy four days after plasmapheresis and an uneventful surgery. CONCLUSION This case highlights the complexities in the management of thyroid storm, and the risk of relapse despite initial biochemical and clinical improvement. A sufficient course of plasmapheresis is essential to allow for urgent thyroidectomy.